Synthesis of Uracil Derivatives and Some of Their Reactions - Barmaki, M.; Maharramov, A.M.; Allahverdiyev, M.E. (Asian Journal of Chemistry, 2010)
An efficient one-pot synthesis of 1-phenylcarbamide-3- hydroxy-4,6-pyrimidine-[2,3-a]-5'-hydroxytetrahydro-1,3- thiazine is described. The synthesis is based on the reaction of ethyl cyanoacetate and thiocarbamide in the presence of sodium acetate. The cyclized compounds react with 1,2- epoxychloropropane then treated in medium of ethyl alcohol in peresence of KOH, which recyclized product 1-amino-3- hydroxy-4,6-pyrimidine-[2,3-a]-5'-hydroxy-tetrahydro-1,3- thiazine produced. In the final reaction, this product with phenylisocyanate give a side chain reaction of the obtained 1-phenylcarbamide-3-hydroxy-4,6-pyrimidine-[2,3-a] -5'- hydroxytetrahydro-1,3-thiazine.